SUPERNATURALISM AND MYSTICISM IN WILLIAM SHAKESPEARE’S PLAY HAMLET - Nurmalasari, Muharrani; Adha, Ruly (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2016)
William Shakespeare is the greatest dramatist in the world. He has produced a lot of literary works especially play or drama. Some of his plays still exist until now such as Julius Caesar, Hamlet, The Merchant of Venice, etc. Even, one of his plays Romeo and Juliet has been translated into several languages in the world. He produces two types of plays, namely comedy which usually talks about love and tragedy which talks about sadness. In tragedy plays, Shakespeare always puts supernatural and mystical elements such as in Julius Caesar, Macbeth, Hamlet, etc. The supernatural and mysticism elements are usually marked by the appearance of apparition, witch, fairy, etc, and the elements can determine the fate of main characters. This article tries to describe how Shakespeare puts supernatural and mystical elements in one of his tragedy plays Hamlet.